2015
DOI: 10.1149/2.0401509jes
|View full text |Cite
|
Sign up to set email alerts
|

Method Development for Quantitative Analysis of Actinides in Molten Salts

Abstract: This paper describes how electrochemical techniques have been used to develop a method for high-precision, real-time quantitative measurements of the concentration of actinides, present in in molten salts as actinide chlorides, for pyrochemical process monitoring applications. Possible reasons for discrepancies between reported measurements obtained with electrochemical techniques have been investigated and a combination of methods to improve their precision has been established. The combination of methods con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 60 publications
5
62
0
Order By: Relevance
“…Average values of diffusion coefficients were calculated for both elements, and are shown in Table II. The diffusion coefficients calculated from nucleation data are consistent with values obtained using CV in our previous work 29,30 as well as with the values reported in the literature. [45][46][47] In addition to this, the value of U(III) diffusion was compared with the results obtained by Kwon et al using first principles computational models and the values were found to be in Relationship between nucleation rate and overpotential for salt compositions 2 (0.95 wt% U) and 4 (1.33 ± 0.13 wt% Pu), shown in Table I. very good agreement.…”
Section: +supporting
confidence: 91%
See 1 more Smart Citation
“…Average values of diffusion coefficients were calculated for both elements, and are shown in Table II. The diffusion coefficients calculated from nucleation data are consistent with values obtained using CV in our previous work 29,30 as well as with the values reported in the literature. [45][46][47] In addition to this, the value of U(III) diffusion was compared with the results obtained by Kwon et al using first principles computational models and the values were found to be in Relationship between nucleation rate and overpotential for salt compositions 2 (0.95 wt% U) and 4 (1.33 ± 0.13 wt% Pu), shown in Table I. very good agreement.…”
Section: +supporting
confidence: 91%
“…The surface area of the working electrode was determined by standard addition method, which is described in more detail in our previous report. 29 For tests on salts containing U 3+ ions, a layer of uranium metal predeposited on the walls of the crucible served as the counter electrode to ensure that the counter reaction did not interfere with the reaction occurring at the WE. For tests on salts containing Pu 3+ ions (salt composition 4 in Table I), a second tungsten wire with a 0.2032-cm diameter was used as a counter electrode.…”
Section: Methodsmentioning
confidence: 99%
“…Concentration calculations.-To calculate the concentration of U 3+ in the salt, we used the standard area addition described in detail in our previous work. 1 In this method, the peak currents are plotted as a function of the controlled immersion depth (h) of the working electrode, and from the slope of a generated linear plot ( i p h ) described by Equation 2, the concentration C i is calculated.…”
Section: Resultsmentioning
confidence: 99%
“…2 The setup consisted of an Inconel crucible containing molten salt into which the electrodes were immersed. The working and quasireference electrodes were 1 mm diameter tungsten rods, and the counter electrode was * Electrochemical Society Member.…”
Section: Methodsmentioning
confidence: 99%
“…Electroanalytical techniques using cyclic voltammograms (CVs) are a promising approach that has been developed to provide these measurements. [1][2][3][4] Earlier voltammetry studies showed that CVs were able to provide very accurate results at low concentrations (0-2 wt%) for molten chloride salts containing U and Pu;…”
mentioning
confidence: 99%